Alterations in the fecal microbiota in patients with advanced cystic fibrosis liver disease after 6 months of elexacaftor/tezacaftor/ivacaftor - Duong, Jennifer T; Pope, Christopher E; Hayden, Hillary S; Miller, Carson; Salipante, Stephen J; Rowe, Steven M; Solomon, George M; Nichols, David; Hoffman, Lucas R; Narkewicz, Michael R; Green, Nicole (Journal of cystic fibrosis, 2024)
•aCFLD had higher S. salivarius and V. parvula fecal abundances compared to CFnoLD.•Both species decreased after ETI in subjects with aCFLD and calprotectin decrease.•This supports the gut-liver axis linking dysbiosis, intestinal inflammation & aCFLD. Cystic fibrosis associated liver disease (CFLD) carries a significant disease burden with no effective preventive therapies. According to the gut-liver axis hypothesis for CFLD pathogenesis, dysbiosis and increased intestinal inflammation and permeability permit pathogenic bacterial translocation into the portal circulation, leading to hepatic inflammation and fibrosis. Evaluating the effect of CFTR (cystic fibrosis transmembrane conductance regulator) modulation with elexacaftor/tezacaftor/ivacaftor (ETI) may help determine the role of CFTR in CFLD and increase understanding of CFLD pathogenesis, which is critical for developing therapies. We aimed to characterize the fecal microbiota in participants with CF with and without advanced CFLD (aCFLD) before and after ETI. This is an ancillary analysis of stool samples from participants ages ≥12 y/o enrolled in PROMISE (NCT04038047). Included participants had aCFLD (cirrhosis with or without portal hypertension, or non-cirrhotic portal hypertension) or CF without liver disease (CFnoLD). Fecal microbiota were defined by shotgun metagenomic sequencing at baseline and 1 and 6 months post-ETI. We analyzed 93 samples from 34 participants (11 aCFLD and 23 CFnoLD). Compared to CFnoLD, aCFLD had significantly higher baseline relative abundances of potential pathogens Streptococcus salivarius and Veillonella parvula. Four of 11 aCFLD participants had an initially abnormal fecal calprotectin that normalized 6 months post-ETI, correlating with a significant decrease in S. salivarius and a trend towards decreasing V. parvula. These results support an association between dysbiosis and intestinal inflammation in CFLD with improvements in both post-ETI, lending further support to the gut-liver axis in aCFLD.